Diseño, instalación y evaluación de un sistema de riego por goteo y micro aspersión en el predio "La Dolorosa" de la parroquia Chuquiribamba, cantón y provincia de Loja - Aguinsaca Medina, Diana Elizabeth (2020)
This present work: "Design, installation and evaluation of a drip and micro sprinkler irrigation system on the "La Dolorosa” sector, in the Chuquiribamba parish, Loja's canton and province, it has the main objective contributing to the efficient management of soil and water for irrigation, through the design, installation and field evaluation of a drip and micro sprinkler irrigation systems. The implementation of two irrigation methods were planned (drip and micro sprinkling) initially; however, the farmer's requirements led to the implementation sprinkler irrigation system additional, the 3 subsystems were designed to 3,900 m2 irrigate, this area is intended for 3 crops (apple, tree tomato and grass). This study contemplates two design phases: the agronomic design, based on soil's factors, field's data, infiltration and evapotranspiration; and, on the other hand, the hydraulic design whose series of calculations allowed the dimensioning of pipes and the flow network with all the accessories that make it up, for this series of calculations the following information was available: i) INAMHI's Climate information by stations meteorological, ii) Laboratory's data on: water and soil, provided by the "Honorable Consejo Provincial de Loja" and the UNL's Laboratory of soils, ii) irrigation materials and equipment's catalogs, and iv) Other data collected in the field such as: flow, topography, water pressure column. With the agronomic design, the irrigation method for each crop was determined, drip for tree tomato, micro sprinkling for apple and sprinkling for forage, with irrigation time of 1, 2 and 4 hours respectively, and a frequency of 4 days. This frequency was predetermined by the watering shifts set by "Junta de Riego del sector - La Dolorosa". For the installation of the irrigation system, it was necessary to carry out land adaptation works, including: the construction of beds in level curve, weed cleaning, clearing and excavation of ditches, the connections of pipes and accessories were made with labor qualified to subsequently carry out an field evaluation of the already installed system, this evaluation began with a visual inspection that was carried out from the reservoir to each of the emitters that make up the system, having verified that there ween't leaks, damages or deterioration of the elements the system, the Christiansen Uniformity Coefficient methodology was applied, resulting a value of over 90% for both the drip and the micro-spray methods. This indicator confirmed designs adequate and that the system works normally; for sprinkling method, the pressures at each connection of the emitter were measured, noting that there was no greater variation with respect to each other. Along with the design, a use and maintenance manual was prepared in order to guarantee irrigation efficiency and keep all the components irrigation system’s in the best working conditions. Key words: Design, installation, evaluation, manual, irrigation.